Implementasi Nilai-Nilai Budaya Kearifan Lokal Bugis-Makassar dalam Mengembangkan Aspek Nilai Moral pada Anak Usia 5-6 Tahun - Ratnasari; Musi, Muhammad Akil; Lismayani, Angri (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2025)
This study aims to analyze the Implementation of Local Wisdom Cultural Values ​​of Bugis-Makassar in TK Aisyiyah Bustanul Athfal III Karunrung, Makassar City. The purpose of this study is to see the application of local wisdom culture of Bugis-Makassar in developing aspects of moral values ​​in children aged 5-6 years. The approach used in this study is a qualitative approach, with a descriptive research type. The data sources in this study were the Principal, Teachers, and Children aged 5-6 years. Data collection techniques were in the form of interviews, observations, and documentation. Data analysis techniques used data collection, data reduction, data presentation, and conclusions. The results of this study indicate that there are effective changes in the moral value aspects of children aged 5-6 years through the implementation of local cultural values ​​of Bugis-Makassar such as sipakatatau (mutual respect), sipakalebbi (mutual appreciation), sipakainge' (mutual reminder), lempu'/lambusu' (honesty), reso/akkareso (trying or being responsible), and assamaturu'/situlung-tulung (helping each other or mutual cooperation) at Aisyiyah Bustanul Athfal III Karunrung Kindergarten, Makassar City. A total of 11 children (73%) have developed Very Well, 3 children (20%) have developed according to expectations, and 1 child (7%) has started to develop. These cultural values ​​are implemented informally through habituation methods, role model methods, and character strengthening methods through social interaction.